Global supply chain risk management strategies: A case study - Kravchenko, Anastasia (My University, 2017)
Growing complexity of the global environment and the appearance of new risks in a supply chain increase the uncertainty of companies’ operations and the possibility for failure in performance. However, many companies nowadays are not well prepared to handle risks that may become an obstacle to their goals. As a result, company managers are searching for strategies to overcome difficulties. Supply chain risk management is one of the fastest growing fields of logistics research aimed to create innovative methods to risk mitigation and prevention, improve the financial performance and bring the competitive advantage. Thus, the purpose of this study is to provide explanation for significance of risk management integration in company operations and demonstrate how the choice of appropriate risk management strategy should be made in order to mitigate possible consequences and predict adverse events. The author built the theoretical framework for the SCRM system upon the literature overview for the company with international suppliers. It includes ten steps from risk identification and evaluation to the possibility of cooperation with partners in a supply chain for mutual efforts. The study is of qualitative type with in-depth analysis of a single case. The empirical data have been collected through 7 face-to-face semi-structured interviews with managers from the case companies and 11 questionnaires answered by managers from the supplier companies. The findings suggest that demand and operational risk types are the most important for the trading company operation and should be controlled primarily. Despite only few companies have established the full-size SCRM system, they are aware of risk consequences and implemented the range of strategies to mitigate risks and forecast their appearance in the future. The author contributed to the field by developing the list of SCRM strategies relevant to risk types they can handle.
Keywords: risk management; global supply chain; strategy implementation; theoretical framework; single case study; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|